Апокалиптическая аллюзия как структурообразующий компонент в повести М. А. Булгакова «Роковые яйца» - Kaloh Vid, Natalia (Slavia Centralis, 2020)
This research study builds on the analysis of the apocalyptic vision in Mikhail Bulgakov’s science fiction short story Fatal Eggs. The apocalyptic vision of reality defines the writer’s artistic world, as the plot of the story is built as an ambivalent projection of the biblical story of the end of the world in the Book of Revelation. Bulgakov uses various inter-textual figures to refer to this biblical text, with allusions serving as the most important. In his futuristic perspective, the author shows the consequences of the new politics of socialism, as well as new methods of constructing a contemporary society. Bulgakov offers his readers a horrible perspective of the future in which human beings become mere test subjects for an experiment. Bulgakov uses typical features of dystopia: state control of literature and art, apocalyptic atmosphere, and the position of those who do not want to become "the same-thinking machines" and thus have no perspective in a new society. The analysis focuses on the use and meaning of key ambivalent allusions to the New Jerusalem and Babylon, the apocalyptic Beast, God’s seals, resurrection and God, the Creator.